Back Cover: Engineering the Electrochemical Capacitive Properties of Graphene Sheets in Ionic‐Liquid Electrolytes by Correct Selection of Anions (ChemSusChem 11/2014). Issue 11 (16th October 2014) - Shi, Minjie; Kou, Shengzhong; Yan, Xingbin
<x xml:space="preserve">Abstract</x> The Back Cover picture shows the electrochemical double layer capacitor behavior of graphene sheets in ionic liquids. In these ionic liquids the same cation has been coupled with different anions. Prof. Yan et al. systematically studied the relationship between the anion characteristics of ionic liquids and the electrochemical performance of graphene sheets. Moreover, they deeply analyzed the inherent reason and the mechanism influencing energy density and cycling stability of graphene sheets in ionic liquids. More details can be found in their Full Paper on page 3053 (DOI: 10.1002/cssc.201402275).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>